The Profile of the Upper Secondary School English Languge Teachers' Pedagogic and Professional Competences - Maximus Leonardus Nemo; Gunadi Harry Sulistyo; Johannes Ananto Prayogo (Universitas Negeri Malang, 2019)
Abstract: This research aims at identifying EFL teahcer's pedagogic competence and professional competence of EFL Teachers in 5 Districts in the Municipality of Jayapura, Papua Province. The research method was survey. Questionnaire was used to collect data. The number of respondents were 46 of EFL teachers from 38 upper secondary schools. The data analysis shows that based on the range of the category of the total score it was found that more than half of the respondents fall into high category, and less than half of the respondents fall into moderate category. None of the respondents falls into low category.  For pedagogic category, two-thirds of respondents fall on the moderate category, and one-third of the respondents fall on high category. Non of the respondents falls on low category. For professional category, almost two-third of the respondents fall on high category, and more than one-thids of the respondents fall on the moderate category. Only one respondent falls into low category. From all these findings, it was also found that all the teachers in Jayapura in general are more competent in professional category than in pedagogy. Key Words: english language teachers, pedagogic competence, professional competence Abstrak: Penelitian ini bertujuan untuk mengetahui kompetensi pedagogi dan profesional guru-guru bahasa Inggris di 5 Distrik kota Jayapura, Provinsi Papua. Metode penelitian ini adalah Survey. Pengumpulan data menggunakan quesioner .Jumlah respoden adalah 46 guru dari 38 SMA/K. Data analisis menunjukkan skor total lebih dari setengah responden berada pada kategori tinggi, dan kurang dari setengah responden berada pada kategory sedang. Tidak ada responden yang berada pada kategori rendah. Untuk pedagogi hampir 2/3 responden berada pada kategori tinggi dan lebih dari 1/3 responden berada pada kategori rendah. Tidak ada responden yang berada pada kategori rendah. Untuk profesional hampir 2/3 responden berada pada kategori tinggi, dan lebih dari 1/3 responden berada pada kategori sedang. Hanya ada satu responden yang berada pada kategori rendah. Dari keseluruhan temuan, dapat juga ditemukan bahwa semua responden guru bahasa Inggris di Kota Jayapura pada umumnya lebih mampu di kategori profesional daripada di pedagogi. Kata kunci: guru bahasa Inggris, kompetensi pedagogi, kompetensi profesional